Surface-etched aluminum fiber current collector and continuous preparation method and application thereof

By etching the porous structure of the aluminum fiber current collector on the surface, the problem of insufficient adhesion of existing aluminum foil and foam aluminum in lithium batteries is solved, and the rate performance, low temperature performance and cycle life of the electrode are significantly improved.

CN119650705APending Publication Date: 2025-03-18CHANGCHUN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411860362.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The insufficient adhesion of existing aluminum foil and foam aluminum in lithium batteries leads to rapid attenuation of battery capacity and cycle life, making it difficult to improve the rate performance, low temperature performance and cycle life of the electrode.

Method used

The surface etched aluminum fiber current collector is used, which forms a porous structure through ultrasonic cleaning, ultrasonic etching and drying treatment, which significantly improves adhesion with the electrode slurry, and enhances conductivity and electrolyte wetting.

Benefits of technology

The rate performance, low temperature performance and cycle life of the electrode are significantly improved, solving the limitations of aluminum foil and foam aluminum in terms of adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650705A_ABST
    Figure CN119650705A_ABST
Patent Text Reader

Abstract

The invention provides a surface-etched aluminum fiber current collector and a continuous preparation method and application thereof, and belongs to the technical field of current collector materials. The surface of the surface-etched aluminum fiber current collector prepared by the method provided by the invention has a porous structure, so that the adhesive force between the surface-etched aluminum fiber current collector and electrode slurry is remarkably improved, the conductivity is enhanced, and the limitation of commercial aluminum foil and foamed aluminum in the aspect of adhesive force is effectively solved; and the surface-etched aluminum fiber current collector with the porous structure shows good electrolyte wettability, the rate capability and low-temperature performance of an electrode are effectively improved, the cycle life of the electrode is effectively prolonged, and commercial aluminum foil and foamed aluminum are difficult to realize. The surface-etched aluminum fiber current collector prepared by the method can be widely applied to electrode preparation of lithium ion batteries, sodium ion batteries and / or zinc ion batteries, and has important commercial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of current collector materials, and in particular to a surface-etched aluminum fiber current collector and a continuous preparation method and application thereof. Background Art

[0002] In the manufacture of lithium batteries, the current collector is an important component of the battery cell and plays the role of loading the positive and negative active materials. It is very important to choose a suitable current collector. In addition to the common copper current collector, there are many other materials to choose from, such as aluminum current collector. Although the conductivity of aluminum is slightly inferior to that of copper, it is light in weight and is an ideal choice for improving the energy density of the battery. Aluminum current collectors will form a dense oxide film during the charge and discharge process, which enhances its corrosion resistance and is particularly suitable as a positive electrode current collector. Traditional aluminum foil and etched aluminum foil current collectors usually have a certain rigidity and a limited contact area with the positive electrode material, which affects the internal resistance. The bonding strength of aluminum foil with binders and active materials is limited, which can easily lead to loose bonding between particulate matter and easy powder loss during cyclic charge and discharge, causing the battery capacity and cycle life to decay rapidly. These problems limit the improvement of battery performance. Therefore, how to effectively solve the limitations of commercial aluminum foil and foamed aluminum in terms of adhesion, and provide an aluminum current collector with good electrolyte wettability to effectively improve the rate performance, low temperature performance and cycle life of the electrode is a technical problem that the prior art urgently needs to solve. Summary of the invention

[0003] The purpose of the present invention is to provide a surface etched aluminum fiber current collector and a continuous preparation method and application thereof. The preparation method provided by the present invention can prepare a surface etched aluminum fiber current collector having a porous surface structure, which enhances the adhesion with the electrode slurry and provides excellent conductivity. In addition, the porous structure thereof enables it to exhibit good electrolyte wettability, effectively improving the rate performance, low temperature performance and cycle life of the electrode.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a continuous preparation method of a surface-etched aluminum fiber current collector, comprising the following steps:

[0006] S1, performing a first ultrasonic cleaning and a first rinsing on the aluminum fiber current collector in sequence to obtain a cleaned aluminum fiber current collector;

[0007] S2, ultrasonically etching the cleaned aluminum fiber current collector obtained in step S1 to obtain an etched aluminum fiber current collector;

[0008] S3, subjecting the etched aluminum fiber current collector obtained in step S2 to a second rinsing and drying treatment in sequence to obtain a surface-etched aluminum fiber current collector;

[0009] In the steps S1, S2 and S3, the corresponding aluminum fiber current collectors are transported using a transport device.

[0010] Preferably, the conveying speed is 0.07-1.5 m / min -1 .

[0011] Preferably, the reagents used for the first ultrasonic cleaning and the first rinsing in step S1 are independently at least one of deionized water, acetone, ethanol, and a solution containing a surfactant.

[0012] Preferably, the power density of the first ultrasonic cleaning in step S1 is 0.1-5 W / cm 2 , the length of the first ultrasonic cleaning tank is 1 to 2 m.

[0013] Preferably, the temperature of the ultrasonic etching in step S2 is 18-90° C., and the power density of the ultrasonic etching is 0.1-5 W / cm 2 , the length of the ultrasonic etching groove is 0.8 to 6 m.

[0014] Preferably, the etching solution used for ultrasonic etching in step S2 is a ferric chloride solution, and the concentration of ferric chloride in the ferric chloride solution is 0.1-5 mol / L.

[0015] Preferably, the reagent used for the second elution in step S3 is at least one of deionized water and ethanol, and the length of the second elution tank is 0.5 to 2 m.

[0016] Preferably, the drying process in step S3 is low-temperature blast drying; the temperature of the drying process is room temperature to 60° C., the length of the operating zone of the drying process is 1 to 5 m, and the blast wind speed of the drying process is 0.1 to 5 m / s.

[0017] The present invention also provides a surface-etched aluminum fiber current collector prepared by the continuous preparation method described in the above technical scheme, wherein the metal fiber surface of the surface-etched aluminum fiber current collector has a porous structure, and the pore size of the porous structure is in the micrometer to nanometer level.

[0018] The present invention also provides the use of the surface-etched aluminum fiber current collector described in the above technical solution in the preparation of battery electrodes.

[0019] The continuous preparation method provided by the present invention has a porous structure on the surface of the surface-etched aluminum fiber current collector, which significantly improves its adhesion to the electrode slurry and enhances its conductivity, effectively solving the limitations of commercial aluminum foil and foamed aluminum in terms of adhesion; and the surface-etched aluminum fiber current collector with a porous structure exhibits good electrolyte wettability, effectively improving the rate performance, low temperature performance and cycle life of the electrode, which is difficult to achieve with commercial aluminum foil and foamed aluminum. The surface-etched aluminum fiber current collector prepared by the present invention can be widely used in the preparation of electrodes for lithium-ion batteries, sodium-ion batteries and / or zinc-ion batteries, and has important commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the surface of the surface-etched aluminum fiber current collector prepared in Example 1 of the present invention;

[0021] Figure 2 The cycle performance diagram of the lithium ion battery assembled with the surface-etched aluminum fiber current collector prepared in Example 2, the aluminum foil current collector prepared in Comparative Example 1, and the unetched aluminum fiber current collector prepared in Comparative Example 2;

[0022] Figure 3 The cycle performance diagram of the sodium ion battery assembled with the surface-etched aluminum fiber current collector prepared in Example 4, the aluminum foil current collector prepared in Comparative Example 3, and the unetched aluminum fiber current collector prepared in Comparative Example 4;

[0023] Figure 4 A comparison diagram of the contact angles of the pole pieces after the surface-etched aluminum fiber current collector prepared in Example 2, the aluminum foil current collector prepared in Comparative Example 1, and the unetched aluminum fiber current collector prepared in Comparative Example 2 were coated with slurry;

[0024] Figure 5 This is a comparison chart of the electrode sheet resistivity after coating the slurry on the surface-etched aluminum fiber current collector prepared in Example 4, the aluminum foil current collector prepared in Comparative Example 3, and the unetched aluminum fiber current collector prepared in Comparative Example 4. DETAILED DESCRIPTION

[0025] The present invention provides a continuous preparation method of a surface-etched aluminum fiber current collector, comprising the following steps:

[0026] S1, performing a first ultrasonic cleaning and a first rinsing on the aluminum fiber current collector in sequence to obtain a cleaned aluminum fiber current collector;

[0027] S2, ultrasonically etching the cleaned aluminum fiber current collector obtained in step S1 to obtain an etched aluminum fiber current collector;

[0028] S3, subjecting the etched aluminum fiber current collector obtained in step S2 to a second rinsing and drying treatment in sequence to obtain a surface-etched aluminum fiber current collector;

[0029] In the steps S1, S2 and S3, the corresponding aluminum fiber current collectors are transported using a transport device.

[0030] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.

[0031] The present invention sequentially performs a first ultrasonic cleaning and a first rinsing on the aluminum fiber current collector to obtain a cleaned aluminum fiber current collector.

[0032] In the present invention, the reagents used for the first ultrasonic cleaning and the first rinsing are preferably independently at least one of deionized water, acetone, ethanol, and a solution containing a surfactant. In the present invention, the surfactant in the solution containing a surfactant is preferably one or more of dodecylbenzenesulfonic acid, nonylphenol polyoxyethylene ether, and fatty alcohol polyoxyethylene ether. In the present invention, the power density of the first ultrasonic cleaning is preferably 0.1 to 5 W / cm 2 , the length of the first ultrasonic cleaning tank is preferably 1 to 2 m. The present invention removes oil from the surface by the first ultrasonic cleaning, which is convenient for subsequent etching. In the present invention, the length of the first rinsing tank is preferably 0.5 to 2 m, more preferably 1 m. The present invention removes residual impurities and reagents by the first rinsing.

[0033] After obtaining the cleaned aluminum fiber current collector, the present invention performs ultrasonic etching on the cleaned aluminum fiber current collector to obtain an etched aluminum fiber current collector.

[0034] In the present invention, the temperature of the ultrasonic etching is preferably 18 to 90°C, more preferably 20 to 80°C; the power density of the ultrasonic etching is preferably 0.1 to 5 W / cm 2 , the length of the ultrasonic etching groove is preferably 0.8 to 6 m, more preferably 1 to 5 m. In the present invention, the etching solution used for the ultrasonic etching is preferably a ferric chloride solution, and the concentration of ferric chloride in the ferric chloride solution is preferably 0.1 to 5 mol / L. The present invention controls the parameters of ultrasonic etching within the above range to achieve the formation of a porous structure with a pore size of micrometer to nanometer on the surface of the metal fiber of the prepared surface-etched aluminum fiber current collector, which can significantly improve its adhesion to the electrode slurry, enhance conductivity, and improve the wettability of the electrolyte, thereby improving the rate performance, low temperature performance and cycle life of the battery.

[0035] After obtaining the etched aluminum fiber current collector, the present invention sequentially performs a second rinsing and drying treatment on the etched aluminum fiber current collector to obtain a surface-etched aluminum fiber current collector.

[0036] In the present invention, the reagent used for the second elution is preferably at least one of deionized water and ethanol; the length of the second elution tank is preferably 0.5 to 2 m, more preferably 1 m. The present invention removes solid impurity particles and the like on the surface of the etched aluminum fiber current collector through the second elution.

[0037] In the present invention, the drying process is preferably low-temperature blast drying; the drying process temperature is preferably room temperature to 60°C, the length of the drying process operation zone is preferably 1 to 5 m, and the blast wind speed of the drying process is preferably 0.1 to 5 m / s. The present invention removes residual reagents through drying process.

[0038] In the present invention, the conveying speed is preferably 0.07 to 1.5 m / min. -1 , more preferably 0.1 to 1 m / min -1 The present invention controls the conveying speed within the above range to regulate the conveying speed of the aluminum fiber current collector, and coordinately controls the length of the first ultrasonic cleaning tank, the length of the ultrasonic etching tank, the length of the second rinsing tank, and the length of the drying treatment operation area to achieve better ultrasonic etching, rinsing and drying effects, thereby obtaining a surface-etched aluminum fiber current collector with better performance.

[0039] The present invention also provides a surface-etched aluminum fiber current collector prepared by the continuous preparation method described in the above technical solution.

[0040] In the present invention, the surface of the metal fiber of the surface-etched aluminum fiber current collector has a porous structure, and the pore size of the porous structure is in the micrometer to nanometer level.

[0041] The present invention also provides the use of the surface-etched aluminum fiber current collector described in the above technical solution in the preparation of battery electrodes.

[0042] In the present invention, the battery is preferably a lithium ion battery, a sodium ion battery and / or a zinc ion battery.

[0043] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] A continuous preparation method for a surface-etched aluminum fiber current collector, comprising the following steps:

[0046] S1. Use a continuous conveying device to conduct a first ultrasonic cleaning of the aluminum fiber current collector through an acetone solution in a first ultrasonic cleaning tank to achieve surface degreasing, and then conduct a first rinsing with deionized water in a first rinsing tank to obtain a cleaned aluminum fiber current collector; wherein the length of the first ultrasonic cleaning tank is 2 m, the length of the first rinsing tank is 1 m, and the conveying speed of the continuous conveying device is 0.1 m / min -1 ;

[0047] S2, continue to use the continuous conveying device to pass the cleaned aluminum fiber current collector obtained in step S1 into the ultrasonic etching tank, use 0.8 mol / L ferric chloride solution as the etching solution, control the ultrasonic etching temperature at 60°C, and the ultrasonic etching power density is 0.4 W / cm 2 , the length of the ultrasonic heating etching groove is 2.5m, ultrasonic etching is performed to obtain an etched aluminum fiber current collector;

[0048] S3. Continue to use the continuous conveying device to pass the etched aluminum fiber current collector obtained in step S2 into the second rinsing tank, use deionized water for the second rinsing to remove surface residues, the length of the second rinsing tank is 1m, and the aluminum fiber current collector after the second rinsing is subjected to low-temperature blast drying. The temperature is controlled at 40°C, the length of the drying operation zone is 2m, and the blast wind speed is 2m / s to obtain a surface etched aluminum fiber current collector.

[0049] The positive electrode active material LiFePO4 is mixed and homogenized with the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry. The positive electrode material slurry is coated on the surface-etched aluminum fiber current collector prepared in Example 1 after cutting and welding with aluminum pole ears. After oscillation until the slurry is completely filled, it is dried in an oven at 100°C for 12 hours to obtain a positive electrode sheet. The prepared positive electrode sheet is assembled into a lithium-ion battery with a metal lithium negative electrode and a lithium-ion secondary electrolyte (LB-275), and the cycle performance of the assembled lithium-ion battery is tested. The test results show that after 200 cycles at a rate of 1C, there is still 132mAh·g -1 discharge capacity.

[0050] The above embodiments show the specific operation steps of the method of the present invention. By adjusting the concentration and temperature of the ultrasonic cleaning solution and the etching solution, the performance of the current collector can be optimized. These embodiments are only examples, and those skilled in the art can adjust the method parameters according to actual needs to obtain the best effect.

[0051] Embodiment 2:

[0052] A continuous preparation method for a surface-etched aluminum fiber current collector, comprising the following steps:

[0053] S1. Use a continuous conveying device to pass the aluminum fiber current collector through the acetone solution in the first ultrasonic cleaning tank for surface degreasing treatment, and then pass it through the first rinsing tank with deionized water for the first rinsing, and the conveying speed is 0.1m / min -1 , wherein the length of the first ultrasonic cleaning tank is 2 m, and the length of the first rinsing tank is 1 m, to obtain the cleaned aluminum fiber current collector;

[0054] S2, passing the cleaned aluminum fiber current collector obtained in step S1 into an ultrasonic etching tank, using 1 mol / L ferric chloride solution as the etching solution, the etching temperature is controlled at 70°C, and the ultrasonic power is 0.6 W / cm 2 , the length of the ultrasonic etching tank is 3m, ultrasonic etching is performed to obtain an etched aluminum fiber current collector;

[0055] S3. Continue to use the continuous conveying device to pass the etched aluminum fiber current collector obtained in step S2 into the second rinsing tank, use deionized water for the second rinsing to remove surface residues, the length of the second rinsing tank is 1m, and the aluminum fiber current collector after the second rinsing is subjected to low-temperature blast drying. The temperature is controlled at 50°C, the length of the drying operation zone is 2m, and the blast wind speed is 3m / s to obtain a surface etched aluminum fiber current collector.

[0056] The positive electrode active material LiMnFePO4 is mixed and homogenized with the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry. The positive electrode material slurry is coated on the surface-etched aluminum fiber current collector prepared in Example 2 after cutting and welding with aluminum pole ears. After oscillation until the slurry is completely filled, it is dried in an oven at 100°C for 12 hours to obtain a positive electrode sheet. The prepared positive electrode sheet is assembled into a lithium-ion battery with a metal lithium negative electrode and a lithium-ion secondary electrolyte (LB-275), and the cycle performance of the assembled lithium-ion battery is tested. The test results show that after 300 cycles at a rate of 1C, there is still 131mAh·g -1 discharge capacity.

[0057] Embodiment 3:

[0058] A continuous preparation method for a surface-etched aluminum fiber current collector, comprising the following steps:

[0059] S1. Use a continuous conveying device to pass the aluminum fiber current collector through the acetone solution in the first ultrasonic cleaning tank for surface degreasing treatment, and then pass it through the first rinsing tank with deionized water for the first rinsing, and the conveying speed is 0.1m / min -1 , wherein the length of the first ultrasonic cleaning tank is 2 m, and the length of the first rinsing tank is 1 m, to obtain the cleaned aluminum fiber current collector;

[0060] S2, passing the cleaned aluminum fiber current collector obtained in step S1 into an ultrasonic etching tank, using 1 mol / L ferric chloride solution as the etching solution, the etching temperature is controlled at 80°C, and the ultrasonic power is 0.8 W / cm 2 , the length of the ultrasonic etching tank is 3m, ultrasonic etching is performed to obtain an etched aluminum fiber current collector;

[0061] S3. Continue to use the continuous conveying device to pass the etched aluminum fiber current collector into the second rinsing tank, rinse with deionized water to remove surface residues. The length of the second rinsing tank is 1m. The aluminum fiber current collector after the second rinsing is subjected to low-temperature blast drying. The temperature is controlled at 60°C. The length of the drying operation zone is 2m. The blast wind speed is 4m / s to obtain a surface etched aluminum fiber current collector.

[0062] The positive electrode active material LiMnFePO4 is mixed and homogenized with the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry, and the positive electrode material slurry is coated on the surface etched aluminum fiber current collector prepared in Example 3 after cutting and welding with aluminum pole ears, and after oscillation until the slurry is completely filled, it is dried in an oven at 100°C for 12 hours to obtain a positive electrode sheet. The prepared positive electrode sheet is assembled into a lithium-ion battery with a metal lithium negative electrode and a lithium-ion secondary electrolyte (LB-002), and the cycle performance of the assembled lithium-ion battery is tested. The test results show that after 200 cycles at a rate of 1C, there is still 130mAh·g -1 discharge capacity.

[0063] Embodiment 4:

[0064] A continuous preparation method for a surface-etched aluminum fiber current collector, comprising the following steps:

[0065] S1. Use a continuous conveying device to pass the aluminum fiber current collector through the acetone solution in the first ultrasonic cleaning tank for surface degreasing treatment, and then pass it through the first rinsing tank with deionized water for the first rinsing, and the conveying speed is 0.1m / min -1 , wherein the length of the first ultrasonic cleaning tank is 2 m, and the length of the first rinsing tank is 1 m, to obtain the cleaned aluminum fiber current collector;

[0066] S2, passing the cleaned aluminum fiber current collector obtained in step S1 into an ultrasonic etching tank, using 1 mol / L ferric chloride solution as the etching solution, the etching temperature is controlled at 75°C, and the ultrasonic power is 0.7 W / cm 2 The length of the first ultrasonic heating etching groove is 3 m, and ultrasonic etching is performed to obtain an etched aluminum fiber current collector;

[0067] S3. Continue to use the continuous conveying device to pass the etched aluminum fiber current collector obtained in step S2 into the second rinsing tank, use deionized water to perform a second rinsing to remove surface residues. The length of the second rinsing tank is 1m. The aluminum fiber current collector after the second rinsing is subjected to low-temperature blast drying. The temperature is controlled at 65°C. The length of the drying operation zone is 2m. The blast wind speed is 3.5m / s to obtain a surface etched aluminum fiber current collector.

[0068] The positive electrode active material Na3V2(PO4)3 is mixed and homogenized with the conductive agent acetylene black, C45 carbon black conductive agent, and binder polyvinylidene fluoride (PVDF) in N-methylpyrrolidone solution at a mass ratio of 93.5:1.5:1.5:3.5 to obtain a positive electrode material slurry, and the positive electrode material slurry is coated on the surface etched aluminum fiber current collector prepared in Example 4 after cutting and welding with aluminum pole ears, and after oscillation until the slurry is completely filled, it is dried in an oven at 100°C for 12 hours to obtain a positive electrode sheet. The prepared positive electrode sheet is assembled into a sodium ion battery with a metal sodium negative electrode and a sodium ion secondary electrolyte (NP-005), and the cycle performance of the assembled lithium ion battery is tested. The test results show that after 200 cycles at a rate of 1C, there is still 101mAh·g -1 discharge capacity.

[0069] Embodiment 5:

[0070] A continuous preparation method for a surface-etched aluminum fiber current collector, comprising the following steps:

[0071] S1. Use a continuous conveying device to pass the aluminum fiber current collector through the acetone solution in the first ultrasonic cleaning tank for surface degreasing treatment, and then pass it through the first rinsing tank with deionized water for the first rinsing, and the conveying speed is 0.1m / min -1 , wherein the length of the first ultrasonic cleaning tank is 2 m, and the length of the first rinsing tank is 1 m, to obtain the cleaned aluminum fiber current collector;

[0072] S2, passing the cleaned aluminum fiber current collector obtained in step S1 (2) into an ultrasonic etching tank, using 1 mol / L ferric chloride solution as the etching solution, the etching temperature is controlled at 80°C, and the ultrasonic power is 0.8 W / cm 2 , the length of the ultrasonic etching tank is 3m, ultrasonic etching is performed to obtain an etched aluminum fiber current collector;

[0073] S3. Continue to use the continuous conveying device to pass the etched aluminum fiber current collector obtained in step S2 into the second rinsing tank, use deionized water for the second rinsing to remove surface residues, the length of the second rinsing tank is 1m, and the aluminum fiber current collector after the second rinsing is subjected to low-temperature blast drying. The temperature is controlled at 75°C, the length of the drying operation zone is 2m, and the blast wind speed is 4.5m / s to obtain a surface etched aluminum fiber current collector.

[0074] The positive electrode active material Na3V2(PO4)3 is mixed and homogenized with the conductive agent acetylene black, C45 carbon black conductive agent, and the binder polyvinylidene fluoride (PVDF) in N-methylpyrrolidone solution at a mass ratio of 93.5:1.5:1.5:3.5 to obtain a positive electrode material slurry. The positive electrode material slurry is coated on the surface-etched aluminum fiber current collector prepared in Example 5 after cutting and welding with aluminum pole ears. After oscillation until the slurry is completely filled, it is dried in an oven at 100°C for 12 hours to obtain a positive electrode sheet; the prepared positive electrode sheet is assembled with a metal sodium negative electrode and a sodium ion secondary electrolyte (LX-153) to form a sodium ion battery, and the cycle performance of the assembled lithium ion battery is tested. The test results show that after 200 cycles at a rate of 1C, there is still 100mAh·g -1 discharge capacity.

[0075] Comparative Example 1:

[0076] Preparation method of aluminum foil current collector, steps:

[0077] (1) Use a continuous conveyor to pass the aluminum foil through an acetone solution in an ultrasonic cleaning tank for surface degreasing treatment, and then rinse it with deionized water in a rinsing tank at a conveying speed of 0.1 m / min. -1 , wherein the length of the first ultrasonic cleaning tank is 2 m, and the length of the elution tank is 1 m, to obtain the eluted aluminum foil current collector;

[0078] (2) Continue to use the continuous conveying device to blow dry the washed aluminum foil current collector obtained in step (1), the temperature is controlled at 50° C., the length of the blow drying operation zone is 2 m, and the blow speed is 3 m / s, to obtain the aluminum foil current collector.

[0079] The positive electrode active material LiMnFePO4, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed and homogenized in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry. The positive electrode material slurry is coated on the aluminum foil current collector prepared in Example 1 after cutting and welding with aluminum pole ears. After oscillation until the slurry is completely filled, it is dried in an oven at 100°C for 12 hours to obtain a positive electrode sheet. The obtained positive electrode sheet is assembled into a lithium ion battery with a metal lithium negative electrode and a lithium ion secondary electrolyte (LB-275), and the cycle performance of the assembled lithium ion battery is tested. The test results show that after 300 cycles at a rate of 1C, there is still 111mAh·g -1 discharge capacity.

[0080] Comparative Example 2:

[0081] A method for preparing an aluminum fiber current collector, comprising the following steps:

[0082] (1) Using a continuous conveying device, the aluminum fiber current collector is passed through an acetone solution in a first ultrasonic cleaning tank for surface degreasing treatment, and then passed through a first rinsing tank for a first rinsing with deionized water. The conveying speed is 0.1 m / min. -1 , wherein the length of the first ultrasonic cleaning tank is 2 m, the length of the first leaching tank is 1 m, and the leached aluminum fiber current collector is obtained;

[0083] (2) The aluminum fiber current collector obtained in step (1) is subjected to air drying after leaching. The temperature is controlled at 50° C., the length of the air drying operation zone is 2 m, and the air speed is 3 m / s to obtain an aluminum fiber current collector.

[0084] The positive electrode active material LiMnFePO4, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were mixed and homogenized in an N-methylpyrrolidone solution at a mass ratio of 93.5:3:3.5 to obtain a positive electrode material slurry, which was coated on the aluminum fiber current collector prepared in Example 2 after cutting and welding with aluminum pole ears, and then oscillated until the slurry was completely filled and dried in an oven at 100°C for 12 hours to obtain a positive electrode sheet; the prepared positive electrode sheet was assembled into a lithium-ion battery with a metal lithium negative electrode and a lithium-ion secondary electrolyte (LB-275), and the cycle performance of the assembled lithium-ion battery was tested. The test results show that after 300 cycles at a rate of 1C, there is still 117mAh·g -1 discharge capacity.

[0085] Comparative Example 3:

[0086] Preparation method of aluminum foil current collector, steps:

[0087] (1) Use a continuous conveyor to remove oil from the surface of the aluminum foil in an acetone solution in an ultrasonic cleaning tank, and then rinse it with deionized water in a rinse tank at a conveying speed of 0.1 m / min. -1 , wherein the length of the first ultrasonic cleaning tank is 2 m, and the length of the elution tank is 1 m, to obtain the eluted aluminum foil current collector;

[0088] (2) The washed aluminum foil current collector obtained in step (1) is subjected to air drying at a temperature of 65° C., a drying length of 2 m, and an air speed of 3.5 m / s to obtain an aluminum foil current collector.

[0089] The positive electrode active material Na3V2(PO4)3 is mixed and homogenized with the conductive agent acetylene black, C45 carbon black conductive agent, and binder polyvinylidene fluoride (PVDF) in N-methylpyrrolidone solution at a mass ratio of 93.5:1.5:1.5:3.5 to obtain a positive electrode material slurry. The positive electrode material slurry is coated on the aluminum foil current collector prepared in Example 3 which is cut and welded with aluminum pole ears. After oscillation until the slurry is completely filled, it is dried in an oven at 100°C for 12 hours to obtain a positive electrode sheet. The prepared positive electrode sheet is assembled with a metal sodium negative electrode and a sodium ion secondary electrolyte (NP-005) to form a sodium ion battery, and the cycle performance of the assembled lithium ion battery is tested. The test results show that after 200 cycles at a rate of 1C, there is still 76mAh·g -1 discharge capacity.

[0090] Comparative Example 4:

[0091] A method for preparing an aluminum fiber current collector, comprising the following steps:

[0092] (1) Using a continuous conveying device, the aluminum fiber current collector is passed through an acetone solution in a first ultrasonic cleaning tank for surface degreasing treatment, and then rinsed with deionized water in a first rinsing tank at a conveying speed of 0.1 m / min. -1 , wherein the length of the first ultrasonic cleaning tank is 2m, the length of the elution tank is 1m, and the eluted aluminum fiber current collector is obtained;

[0093] (2) The aluminum fiber current collector obtained in step (1) was subjected to blast drying at a temperature of 65°C, a drying length of 2m, and a blast wind speed of 3.5m / s to obtain an aluminum fiber current collector. The positive electrode active material Na3V2(PO4)3 was mixed and homogenized with the conductive agent acetylene black, the C45 carbon black conductive agent, and the binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone solution at a mass ratio of 93.5:1.5:1.5:3.5 to obtain a positive electrode material slurry, which was coated on the aluminum fiber current collector prepared in comparative example 4 after cutting and welding with aluminum tabs, and after shaking until the slurry was completely filled, it was dried in an oven at 100°C for 12h to obtain a positive electrode sheet; the prepared positive electrode sheet was assembled into a sodium ion battery with a metal sodium negative electrode and a sodium ion secondary electrolyte (NP-005), and the cycle performance of the assembled lithium ion battery was tested. The test results show that after 200 cycles at a rate of 1C, there is still 87mAh·g -1 discharge capacity.

[0094] Figure 1 This is a SEM image of the surface of the surface-etched aluminum fiber current collector prepared in Example 1. Figure 1 It can be seen that the surface of the surface-etched aluminum fiber collector prepared in Example 1 has an obvious continuous honeycomb-like etched porous structure, in which the etched pore size is 100-150 nm with good uniformity. The high specific surface area and porous structure obtained by etching are conducive to the binding of nano-scale chain binders and improve the bonding strength of the active material coating, thereby providing more stable cycle performance.

[0095] Figure 2 The cycle performance diagram of the lithium ion battery assembled with the surface etched aluminum fiber current collector prepared in Example 2, the aluminum foil current collector prepared in Comparative Example 1, and the unetched aluminum fiber current collector prepared in Comparative Example 2 is shown in FIG. Figure 2 It can be seen that the initial discharge capacity of the three current collectors is similar, all of which are 140 mAhg -1 After 300 cycles at 1C current density, the surface etched aluminum fiber current collector prepared in Example 2 still has 131 mAh g -1 The discharge capacity and discharge capacity retention rate are 93.5%, while the discharge capacity retention rates of Comparative Example 1 and Comparative Example 2 are 79.2% and 83.5%. Therefore, the surface etched aluminum fiber current collector prepared in Example 2 has a better discharge capacity retention rate.

[0096] Figure 3 The cycle performance diagram of the sodium ion battery assembled with the surface-etched aluminum fiber current collector prepared in Example 4, the aluminum foil current collector prepared in Comparative Example 3, and the unetched aluminum fiber current collector prepared in Comparative Example 4 is shown in FIG. Figure 3It can be seen that when the surface-etched aluminum fiber current collector prepared in Example 4 is used as the positive electrode of a sodium ion battery, its initial discharge capacity is 109 mAh g at a current density of 1C. -1 After 200 cycles, the discharge capacity remains at 101 mAh g -1 , while the initial discharge capacities of Comparative Examples 3 and 4 were 85 and 91 mAh g -1 , the discharge capacity after 200 cycles is 76 and 87 mAh g -1 By comparison, it can be seen that the aluminum fiber current collector prepared in Example 4 can stimulate the high activity of the positive electrode material of the sodium ion battery and provide a higher discharge capacity.

[0097] Figure 4 The contact angle comparison diagram of the electrode after the surface-etched aluminum fiber current collector prepared in Example 2, the aluminum foil current collector prepared in Comparative Example 1 and the unetched aluminum fiber current collector prepared in Comparative Example 2 are coated with slurry. Figure 4 It can be seen that the contact angle between the electrode after surface etching of aluminum fiber coating prepared in Example 2 and the electrolyte is 10.758o, and the contact angles of the electrode of the aluminum foil of Comparative Example 1 and the electrode of the unetched aluminum fiber current collector coating of Comparative Example 2 are 24.003 and 17.676o, respectively. Therefore, it is shown that the electrode of surface etched aluminum fiber coating prepared in Example 2 has better wettability with the electrolyte, which is mainly due to the porous structure of aluminum fiber and its large specific surface area. The contact angle of the electrode of unetched aluminum fiber coating is smaller than that of the electrode of aluminum foil, which also shows that the pore structure of aluminum fiber has the effect of increasing the infiltration with electrolyte.

[0098] Figure 5 The resistivity comparison diagram of the electrode sheet after coating the slurry of the surface-etched aluminum fiber current collector prepared in Example 4, the aluminum foil current collector prepared in Comparative Example 3 and the unetched aluminum fiber current collector prepared in Comparative Example 4 is shown in FIG. Figure 5 It can be seen that the resistivity of the surface-etched aluminum fiber coating electrode prepared in Example 4 is 38Ω·μm, the resistivity of the aluminum foil coating electrode of Comparative Example 3 and the un-etched aluminum fiber coating electrode of Comparative Example 4 are 74 and 48Ω·μm, respectively. By comparison, it can be seen that the surface-etched aluminum fiber coating electrode prepared in Example 4 has a smaller resistivity, which is beneficial to the rate discharge performance of the electrode while reducing the energy loss caused by its own resistance.

[0099] In summary, compared with the aluminum foil current collector and the aluminum fiber current collector prepared in the comparative example, the surface etched aluminum fiber current collector prepared by the method provided by the present invention in the embodiment can significantly improve the discharge capacity and cycle life of the battery when used in a lithium-ion battery, and effectively improve the rate performance of the electrode.

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A continuous preparation method for a surface-etched aluminum fiber current collector, characterized in that: The following steps are involved: S1, performing a first ultrasonic cleaning and a first rinsing on the aluminum fiber current collector in sequence to obtain a cleaned aluminum fiber current collector; S2, ultrasonically etching the cleaned aluminum fiber current collector obtained in step S1 to obtain an etched aluminum fiber current collector; S3, subjecting the etched aluminum fiber current collector obtained in step S2 to a second rinsing and drying treatment in sequence to obtain a surface-etched aluminum fiber current collector; In the steps S1, S2 and S3, the corresponding aluminum fiber current collectors are all transported using a transport device.

2. The continuous preparation method according to claim 1, characterized in that: The conveying speed is 0.07-1.5 m / min -1 .

3. The continuous preparation method according to claim 1, characterized in that: The reagents used for the first ultrasonic cleaning and the first rinsing in step S1 are independently at least one of deionized water, acetone, ethanol, and a solution containing a surfactant.

4. The continuous preparation method according to claim 1 or 2, characterized in that: The power density of the first ultrasonic cleaning in step S1 is 0.1-5 W / cm 2 , the length of the first ultrasonic cleaning tank is 1 to 2 m.

5. The continuous preparation method according to claim 1, characterized in that: The temperature of the ultrasonic etching in step S2 is 18-90° C., and the power density of the ultrasonic etching is 0.1-5 W / cm 2 , the length of the ultrasonic etching groove is 0.8 to 6 m.

6. The continuous preparation method according to claim 1 or 5, characterized in that: The etching solution used for ultrasonic etching in step S2 is a ferric chloride solution, and the concentration of ferric chloride in the ferric chloride solution is 0.1-5 mol / L.

7. The continuous preparation method according to claim 1, characterized in that: The reagent used for the second elution in step S3 is at least one of deionized water and ethanol, and the length of the second elution tank is 0.5 to 2 m.

8. The continuous preparation method according to claim 1, characterized in that: The drying process in step S3 is low-temperature blast drying; the temperature of the drying process is room temperature to 60° C., the length of the operation zone of the drying process is 1 to 5 m, and the blast wind speed of the drying process is 0.1 to 5 m / s.

9. The surface-etched aluminum fiber current collector prepared by the continuous preparation method according to any one of claims 1 to 8, characterized in that: The metal fiber surface of the surface-etched aluminum fiber current collector has a porous structure, and the pore size of the porous structure is in the micrometer to nanometer level.

10. Use of the surface etched aluminum fiber current collector according to claim 9 in the preparation of battery electrodes.